The Impact of Alcohol on the Gut Microbiota: A literature review - Jakub Sikora; Karolina Knychalska; Mikołaj Łabuda; Klaudia Królikowska; Aleksandra Słojewska; Agata Kotkowiak; Teresa Sowińska; Oliwia Mentel; Adrianna Bogucka; Agnieszka Szema (Journal of Education, Health and Sport)
Introduction and Purpose The gut microbiota plays a key role in maintaining the body's homeostasis, influencing metabolic, immunological, and neurological processes. Alcohol consumption, particularly in excessive amounts, disrupts the composition and function of the intestinal microbiota, leading to dysbiosis. This article explores the mechanisms by which alcohol affects the gut microbiota and its consequences for overall health. Additionally, it discusses potential therapeutic strategies aimed at mitigating these negative effects.